Recruiting criminal justice majors: Developing a marketing approach - Blankenship, Michael B. (American journal of criminal justice, 1987)
Forecasts suggest the possibility of declining college student enrollment during the next 5–7 years. In order to ensure program survival, a proactive student recruitment program is recommended. This paper outlines the elements of a marketing approach to student recruitment. Moreover, it is suggested that criminal justice departments become more involved in the recruiting process by adopting the marketing elements that fit within budget and personnel allocations. It is further recommended that the time to implement a recruiting program is not after a department’s survival is threatened, but before, in order to avert future difficulties.